(3JGQjN ZRhg Sdje NGf eY bGfUhg GdZhQis - (3CMeO Hf GdMSf Ydj Hf CMeO fhQ GdOjf GdeMdi GdTGaYj GdeYQha HGHf RfHd GdQeGd,J (B980 (3g` s
(3ChdgG (B:s
(3agPG cJGH eTJed Ydi ZRhI GdSdWGf GdCYXe hGdNGbGf GdeQce eGdc QbGH GdCee UGMH GdSja hGdbde s
(3BNQgG (B:s
(3hOaf HGdbQGaI HbQH GdbGVi HcGQ , hCfg cGf ef ChdjGA Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs